Synthesis, characterization, thermal and kinetic properties of chalcone methacrylamide polymers containing halogen group in side chain - Solmaz, Adnan; Ilter, Zulfiye; Kaya, Ismet (Springer, 2022)
In this study, first the chalcone compounds abbreviated as CHAL-F, CHAL-Cl and CHAL-Br containing the halogen group in the side chain were synthesized in medium alkaline at 0 degrees C. Then, chalcone methacrylamide monomers abbreviated as M-F, M-Cl and M-Br containing halogen group in side chain were synthesized by the reaction of the chalcone compounds with methacryloylchloride at 0-5 degrees C in the presence of triethylamine (E3N). The chalcone methacrylamide polymers abbreviated as P-F, P-Cl and P-Br were prepared by the free radical polymerization at 70 degrees C, in DMF solution and by 2,2'-azobisizobutyronitrile (AIBN) initiator. The structures of synthesized compounds were characterized by FTIR, UV-Vis and H-1-C-13-NMR. Thermal characterizations of polymers were performed by thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC). The glass transition temperature (T-g) of P-F, P-Cl and P-Br was found at 103, 129 and 110 degrees C, respectively, from DSC measurements. According to the Flynn-Wall-Ozawa (FWO) method, the average decomposition activation energy of the P-Br was found as 76.84 kJ mol(-1) from the TGA thermograms at different heating rates such as 10, 15 and 20 degrees C min(-1). The contribution of the polar functional groups carried by the synthesized chalcone methacrylamide polymers to some dielectric behavior was examined through the impedance analyzer as a function of frequency. The conductivity values of P-F, P-Cl and P-Br were found 2.00 x 10(-9), 2.04 x 10(-9) and 1.91 x 10(-9) S cm(-1), respectively. The SEM images were used to investigate the morphologies of polymers. The surface morphologies and molecular weight distributions of the polymers were imaged by scanning electron microscopy (SEM) and gel permeation chromatography (GPC), respectively. The optical properties of polymers were investigated by UV-Vis and their antimicrobial activities determined by disk diffusion method. The polymers have exhibited good antimicrobial property against Staphylococcus aureus, Klebsiella pneumonia and have exhibited good antifungal property against Candida albicans.
Keywords: Free radical polymerization; Chalcone; Thermal properties; Dielectric features; Antibacterial activity; Antifungal activity